The cost of preventing undernutrition: cost, cost-efficiency and cost-effectiveness of three cash-based interventions on nutrition outcomes in Dadu, Pakistan. Issue 6 (15th June 2018) - Trenouth, Lani; Colbourn, Timothy; Fenn, Bridget; Pietzsch, Silke; Myatt, Mark; Puett, Chloe
Abstract: Cash-based interventions (CBIs) increasingly are being used to deliver humanitarian assistance and there is growing interest in the cost-effectiveness of cash transfers for preventing undernutrition in emergency contexts. The objectives of this study were to assess the costs, cost-efficiency and cost-effectiveness in achieving nutrition outcomes of three CBIs in southern Pakistan: a 'double cash' (DC) transfer, a 'standard cash' (SC) transfer and a 'fresh food voucher' (FFV) transfer. Cash and FFVs were provided to poor households with children aged 6–48 months for 6 months in 2015. The SC and FFV interventions provided $14 monthly and the DC provided $28 monthly. Cost data were collected via institutional accounting records, interviews, programme observation, document review and household survey. Cost-effectiveness was assessed as cost per case of wasting, stunting and disability-adjusted life year (DALY) averted. Beneficiary costs were higher for the cash groups than the voucher group. Net total cost transfer ratios (TCTRs) were estimated as 1.82 for DC, 2.82 for SC and 2.73 for FFV. Yet, despite the higher operational costs, the FFV TCTR was lower than the SC TCTR when incorporating the participation cost to households, demonstrating the relevance of including beneficiary costs in cost-efficiency estimations. The DC intervention achieved a reduction in wasting, at $4865 per case averted; neither the SC nor the FFV interventions reduced wasting. The cost per case of stunting averted was $1290 for DC, $882 for SC and $883 for FFV. The cost per DALY averted was $641 for DC, $434 for SC and $563 for FFV without discounting or age weighting. These interventions are highly cost-effective by international thresholds. While it is debatable whether these resource requirements represent a feasible or sustainable investment given low health expenditures in Pakistan, these findings may provide justification for continuing Pakistan's investment in national social safety nets.